Manganese dioxide-based positive electrode, positive electrode assembly and aqueous zinc secondary battery comprising the same

The manganese dioxide-based cathode with carbon nanotubes and a cross-linked PAA-PVA binder addresses mechanical issues and adhesion loss, enabling high-loading anodes with enhanced energy density and charge/discharge performance in aqueous zinc secondary batteries.

KR103043153B1Active Publication Date: 2026-11-05KOREA ELECTRONICS TECH INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020210143261
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-26
Publication Date
2026-11-05
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

Aqueous zinc secondary batteries face challenges in achieving high loading amounts of manganese dioxide cathodes without mechanical issues like cracking, and existing binders lose adhesion in water-based electrolytes, leading to reduced energy density and charge/discharge characteristics.

Method used

A manganese dioxide-based cathode comprising carbon nanotubes and a cross-linked copolymer of polyacrylic acid and polyvinyl alcohol as a binder, with specific weight percentages and sizes, allows for a high-loading anode assembly that maintains mechanical integrity and improves charge/discharge characteristics.

Benefits of technology

The solution enables the production of high-loading anodes with improved mechanical properties and charge/discharge characteristics, enhancing energy density and lifespan retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112021122576516-PAT00002_ABST
    Figure 112021122576516-PAT00002_ABST
Patent Text Reader

Abstract

The present invention relates to a manganese dioxide-based cathode capable of improving the physical properties and charge / discharge characteristics of the cathode, a cathode assembly comprising the same, and an aqueous zinc secondary battery. The present invention provides a cathode for an aqueous zinc secondary battery comprising: manganese dioxide; a conductive material containing carbon nanotubes; and a binder containing a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an aqueous zinc secondary battery, and more specifically, to a manganese dioxide-based cathode capable of improving the physical properties and charge / discharge characteristics of the cathode, a cathode assembly comprising the same, and an aqueous zinc secondary battery. Background Technology

[0002] Lithium-ion batteries are one of the most promising technologies for the small and medium-to-large battery markets. However, analyses suggest that limited lithium reserves may not be able to meet increasing demand, and accordingly, the development of next-generation rechargeable batteries is expected to play a significant role in the future energy market.

[0003] In accordance with these market trends, next-generation secondary batteries using sodium (Na) and potassium (K), which are more cost-competitive than lithium, are being developed as alternatives. However, there is a need to develop batteries using multivalent cations capable of accepting one or more electrons to increase the amount of charge reversibly stored in a narrow voltage range. In other words, divalent or trivalent multivalent ions, such as zinc, magnesium, calcium, and aluminum, are expected to achieve higher capacity and energy density than monovalent ions.

[0004] Aqueous zinc secondary batteries are being actively researched and developed for use as energy storage secondary batteries because they can fundamentally resolve the risks of fire and explosion, enable low-cost implementation, and possess low toxicity. An aqueous zinc secondary battery is a system that utilizes zinc metal as the negative electrode active material and manganese dioxide as the positive electrode active material; it utilizes the oxidation / reduction reaction between zinc metal and zinc ions at the negative electrode, and the oxidation / reduction reaction of manganese through the insertion / extraction reaction between zinc ions and hydrogen ions at the positive electrode.

[0005] One of the problems with aqueous zinc secondary batteries containing manganese dioxide as an active cathode material is the manufacturing of the manganese dioxide cathode with a low loading amount (coating amount). That is, approximately 1–2 mg / cm² 2 (Based on the total mass of carbon conductive material and polymer binder other than manganese dioxide) is at the current level, which is approximately 1 mAh / cm² 2 It exhibits the following low capacity per area, which ultimately reduces the energy density of secondary batteries containing it.

[0006] If the anode current collector is coated with a higher loading amount than this, mechanical properties such as cracking of the anode layer occur during drying, making it impossible to manufacture thick anodes.

[0007] Furthermore, since most polymer binders used in the manufacture of anodes lose their adhesion upon contact with water-based electrolytes, the mechanical properties of the anode within the battery also decrease, thereby reducing the battery's charge and discharge characteristics. Prior art literature

[0008] Published Patent Application No. 2021-0086983 (July 9, 2021) The problem to be solved

[0009] Accordingly, the object of the present invention is to a manganese dioxide-based cathode capable of improving physical properties and charge / discharge characteristics while increasing the loading amount of a manganese dioxide-based cathode active material, a cathode assembly including the same, and an aqueous zinc secondary battery. means of solving the problem

[0010] To achieve the above objective, the present invention provides a positive electrode for an aqueous zinc secondary battery comprising: manganese dioxide; a conductive material containing carbon nanotubes; and a binder containing a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol.

[0011] The anode according to the present invention may comprise 70 to 95 wt% of the manganese dioxide, 2 to 20 wt% of the conductive material, and 3 to 10 wt% of the binder.

[0012] The above manganese dioxide has a size of 200 to 900 nm.

[0013] The above carbon nanotube has an average length of 1 μm.

[0014] The anode according to the present invention comprises 2 to 5 wt% of the carbon nanotubes.

[0015] The above conductive material may further include carbon black.

[0016] The above copolymer can be formed by copolymerizing 70 to 95 wt% polyacrylic acid and 5 to 30 wt% polyvinyl alcohol.

[0017] The present invention also provides an anode assembly for an aqueous zinc secondary battery comprising: an anode current collector; and the anode coated on the anode current collector.

[0018] The present invention provides an aqueous zinc secondary battery comprising: a positive current collector and a positive assembly having a positive electrode coated on the positive current collector. Effects of the invention

[0019] According to the present invention, the anode can improve physical properties and charge / discharge characteristics while increasing the loading amount of the anode by including a carbon nanotube based on manganese dioxide and a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol as a binder. Brief explanation of the drawing

[0020] FIG. 1 is a cross-sectional view showing a positive electrode assembly based on manganese dioxide for an aqueous zinc secondary battery according to the present invention. Figure 2 is an SEM image of the anode according to Example 1. Figure 3 is a photograph showing the anode assembly according to Comparative Examples 1 and 2. Figure 4 is a graph comparing the loading amount of the anode according to the example and comparative example. Specific details for implementing the invention

[0021] It should be noted that in the following description, only the parts necessary for understanding the embodiments of the present invention are explained, and the description of other parts will be omitted to the extent that it does not deviate from the gist of the present invention.

[0022] The terms and words used in the specification and claims described below should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention. Accordingly, the embodiments described in this specification and the configurations illustrated in the drawings are merely preferred embodiments of the invention and do not represent all aspects of the technical spirit of the invention; therefore, it should be understood that various equivalents and modifications capable of replacing them may exist at the time of filing this application.

[0023] Hereinafter, embodiments of the present invention will be described in more detail with reference to the attached drawings.

[0024] FIG. 1 is a cross-sectional view showing a positive electrode assembly based on manganese dioxide for an aqueous zinc secondary battery according to the present invention.

[0025] Referring to FIG. 1, the positive electrode assembly (50) for a water-based zinc secondary battery according to the present invention comprises a positive electrode current collector (10) and a positive electrode (20) coated on the positive electrode current collector (10). The positive electrode (20) comprises a conductive material (23) containing manganese dioxide (21) and carbon nanotubes (25), and a binder (29) containing a cross-linked copolymer between polyacrylic acid (PAA) and polyvinyl alcohol (PVA).

[0026] A metal thin film can be used as the positive current collector (10). The metal thin film material may be SUS, Ni, Ti, etc., but is not limited to these.

[0027] The anode (20) comprises 70 to 95 wt% manganese dioxide (21), 2 to 20 wt% conductive material (23), and 3 to 10 wt% binder (29).

[0028] Here, manganese dioxide (21) can have a size of 200 to 900 nm.

[0029] The conductive material (23) may include carbon nanotubes (25). The anode (20) may include 2 to 5 wt% of carbon nanotubes (25). The carbon nanotubes (25) may have an average length of 1 μm. For example, the carbon nanotubes (25) may include at least one selected from single-walled carbon nanotubes, functionalized single-walled carbon nanotubes, double-walled carbon nanotubes, functionalized double-walled carbon nanotubes, multi-walled carbon nanotubes, and functionalized multi-walled carbon nanotubes.

[0030] The conductive material (23) may further include carbon black (27). Other conductive materials (23) may further include VGCF, graphene, Super-P, Super-C, natural graphite, artificial graphite, acetylene black, Ketjen black, furnace black, lamp black, thermal black, etc.

[0031] And the binder (29) comprises a cross-linked copolymer between polyacrylic acid (PAA) and polyvinyl alcohol (PVA). Here, the copolymer may be a cross-linked copolymer between 70 to 95 wt% polyacrylic acid (PAA) and 5 to 30 wt% polyvinyl alcohol (PVA).

[0032] The anode (20) is a thick film manufactured by producing it in the form of a slurry, then applying it to the anode current collector (10) in a coating manner and drying it. In the anode slurry, the manganese dioxide (21), conductive material (23), and binder (29) forming the anode (20) are solids. These solids are dispersed in water, which is a solvent, to produce an anode slurry having an appropriate viscosity. The anode slurry may contain 30 to 40 wt% of solids and 60 to 70 wt% of water.

[0033] At this time, the loading amount of the anode (20) coated on the anode current collector (10) is 10 mg / cm² 2 That is all, 15 mg / cm² 2 It is possible to manufacture high-loading anodes of a certain level.

[0034] In this way, the anode (20) according to the present invention can improve physical properties and charge / discharge characteristics while increasing the loading amount of the anode (20) by including a carbon nanotube (25) based on manganese dioxide (21) and a cross-linked copolymer between polyacrylic acid (PAA) and polyvinyl alcohol (PVA) as a binder (29).

[0035] That is, the anode (20) according to the present invention includes carbon nanotubes (25), thereby enabling the thickening of the anode (20), and thereby increasing the capacity per unit area of ​​the anode (20) and simultaneously improving charge / discharge characteristics.

[0036] In addition, the anode (20) according to the present invention includes a cross-linked copolymer between polyacrylic acid (PAA) and polyvinyl alcohol (PVA) as a binder (29), thereby enabling the anode (20) to be thickened, and thereby increasing the capacity per unit area of ​​the anode (20) and improving the adhesion of the anode (20) to the anode current collector (10), so as to improve the mechanical properties and charge / discharge characteristics of the anode (20).

[0037] [Examples and Comparative Examples]

[0038] In order to verify the loading amount of the anode according to the present invention and the corresponding physical properties and charge / discharge characteristics, anode current collectors according to the examples and comparative examples were manufactured, and the loading amount of the anode and charge / discharge characteristics were measured.

[0039] Example 1

[0040] In Example 1, an anode assembly was prepared by coating an anode slurry containing manganese dioxide, polyacrylic acid (PAA), a polyvinyl alcohol copolymer, and carbon nanotubes (CNT) onto a SUS thin film and then drying it.

[0041] At this time, the size of the manganese dioxide powder is about 300 nm, and the content in the anode is 70 wt%.

[0042] The carbon nanotubes are multi-walled carbon nanotubes with an average length of 1 μm and a content of 4 wt% in the anode. In addition to the carbon nanotubes, the conductive material includes 16 wt% of carbon black to form the electrical network of the anode.

[0043] The binder is a cross-linked copolymer between PAA and PVA, with a molecular weight of PAA of 250,000 and a molecular weight of PVA of 20,000, and a cross-linked binder is applied in a ratio of PAA : PVA = 9 : 1.

[0044] The above-mentioned solid is dispersed in water (H2O) to prepare an anode slurry of appropriate viscosity, then coated onto a SUS thin film, and dried at room temperature and atmospheric pressure to produce an anode assembly.

[0045] Figure 2 is an SEM image of the anode according to Example 1.

[0046] Referring to Fig. 2, an anode formed by coating an anode slurry onto a SUS thin film and then drying it can be seen. It can be seen that the anode has an electrical network formed by including carbon nanotubes.

[0047] Comparative Example 1

[0048] A positive electrode assembly according to Comparative Example 1 was prepared in the same manner as in Example 1, except that carbon nanotubes were not applied to the conductive material. In this case, 20 wt% of carbon black was used as the conductive material.

[0049] Comparative Example 2

[0050] An anode assembly according to Comparative Example 2 was prepared in the same manner as in Example 1, except that PVDF (Polyvinylidene fluoride) was used as the binder.

[0051] FIG. 3 is a photograph showing an anode assembly according to Comparative Examples 1 and 2. FIG. 3(a) shows an anode assembly according to Comparative Example 1, and FIG. 3(b) shows an anode assembly according to Comparative Example 2.

[0052] Referring to FIG. 3, it can be seen that the anode assemblies according to Comparative Examples 1 and 2 are formed unevenly or lifted due to cracking and a decrease in bonding strength on the anode formed on the SUS thin film.

[0053] Figure 4 is a graph comparing the loading amount of the anode according to the example and comparative example.

[0054] Referring to FIG. 4, the loading amount of the anode according to Comparative Example 1 is 3 mg / cm² 2 It is a level of 10 mg / cm² in the case of Comparative Example 1. 2 An anode assembly with the above loading amount was not manufactured. It is believed that as the content of carbon black with a high specific surface area increases, the binding strength of the binder decreases, and additional water is required during the anode slurry manufacturing process. Consequently, mechanical problems such as cracking of the anode and reduced binding strength occur during anode drying, and thus, an anode with a high loading amount is not manufactured.

[0055] The loading amount of the anode according to Comparative Example 2 is 3 mg / cm² 2 It is a level of 7 mg / cm² in the case of Comparative Example 1. 2Anode assemblies with the above loading amount were not manufactured. It is believed that this is because the carbon nanotubes in the NMP used as a solvent were not properly dispersed, and simultaneously, the binding strength of PVDF is lower than that of PAA-PVA. Consequently, mechanical problems such as cracking and reduced binding strength occurred during anode drying, which prevented the production of anodes with high loading.

[0056] On the other hand, the loading amount of the anode according to Example 1 is 15 mg / cm² 2 At a level of 10 mg / cm² 2 The above high-loading anode can be manufactured. As a result, it can be confirmed that the anode according to Example 1 is stably bonded and formed on a SUS thin film, as shown in FIG. 2.

[0057] As can be confirmed from Example 1, Comparative Examples 1 and 2, the anode according to Example 1 contains carbon nanotubes and a PAA-PVA copolymer, thereby producing 10 mg / cm² 2 The above high-loading anode assembly can be manufactured. This is believed to be possible through the uniform dispersion of carbon nanotubes in a water-based anode slurry, the resulting reduction in carbon black content, and the application of a PAA-PVA copolymer binder with excellent binding strength.

[0058] After manufacturing an aqueous zinc secondary battery containing the anode assembly according to Example 1, Comparative Examples 1 and 2, the charge / discharge capacity and lifespan characteristics were evaluated, and the evaluation results are as shown in Table 1.

[0059]

[0060] A water-based zinc secondary battery was manufactured as follows.

[0061] Example 1, Comparative Examples 1 and 2 were used as the anode assembly, and zinc foil was used as the cathode assembly. An aqueous solution of 2M ZnSO4 and 0.1M MnSO4 was used as the electrolyte. Filter paper was used as the separator.

[0062] The aqueous zinc secondary battery is in the form of a single-sheet pouch of the cell type and has dimensions of 3 cm × 4 cm. A constant current of 30 mA / g based on the weight of MnO2 was applied, and the voltage range corresponds to 0.8 to 1.8 V.

[0063] Referring to Table 1, the highest capacity of 180 mAh / g per weight of active material can be confirmed in the anode assembly of Example 1, which uses carbon nanotubes and a PAA-PVA copolymer.

[0064] Therefore, the aqueous zinc secondary battery according to Example 1 has 2 mAh / cm 2 It can be confirmed that it exhibits the highest capacity per unit area, and improved life characteristics can also be observed in terms of life retention rate.

[0065] This is because a high-loading anode could be realized due to well-dispersed carbon nanotubes and a PAA-PVA copolymer binder with excellent binding strength. Furthermore, it is believed that the high capacity and lifespan retention characteristics are achieved not only through the formation of a thick film on the anode but also through the improvement of the electrical network within the anode.

[0066] Meanwhile, the embodiments disclosed in this specification and drawings are merely specific examples provided to aid understanding and are not intended to limit the scope of the invention. It is obvious to those skilled in the art that other variations based on the technical concept of the invention are possible in addition to the embodiments disclosed herein. Explanation of the symbols

[0067] 10: Positive current collector 20 : Anode 21: Manganese dioxide 23 : Challenger 25 : Carbon nanotubes 27 : Carbon Black 29 : Binder 50: Anode assembly

Claims

Claim 1 A cathode for an aqueous zinc secondary battery comprises 70-95 wt% manganese dioxide; 2-20 wt% a conductive material containing carbon nanotubes; and 3-10 wt% a binder containing a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol; wherein the loading amount of the cathode is 10 mg / cm² 2 A positive electrode for an aqueous zinc secondary battery characterized by the above. Claim 2 delete Claim 3 A positive electrode for an aqueous zinc secondary battery according to claim 1, characterized in that the manganese dioxide has a size of 200 to 900 nm. Claim 4 A positive electrode for an aqueous zinc secondary battery according to claim 1, characterized in that the carbon nanotube has an average length of 1 μm and the carbon nanotube is 2 to 5 wt%. Claim 5 A positive electrode for a water-based zinc secondary battery, characterized in that, in claim 1, the conductive material further comprises carbon black. Claim 6 A positive electrode for a water-based zinc secondary battery according to claim 1, characterized in that the copolymer is cross-linked with a composition ratio of 70 to 95 wt% polyacrylic acid and 5 to 30 wt% polyvinyl alcohol. Claim 7 The anode comprises: an anode current collector; and an anode coated on the anode current collector; wherein the anode comprises 70 to 95 wt% manganese dioxide; 2 to 20 wt% a conductive material containing carbon nanotubes; and 3 to 10 wt% a binder containing a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol; and the loading amount of the anode is 10 mg / cm² 2 A positive electrode assembly for a water-based zinc secondary battery characterized by the above. Claim 8 A positive electrode assembly for a water-based zinc secondary battery according to claim 7, wherein the copolymer is cross-linked with a composition ratio of 70 to 95 wt% polyacrylic acid and 5 to 30 wt% polyvinyl alcohol. Claim 9 A positive electrode assembly for an aqueous zinc secondary battery, characterized in that, in claim 8, the carbon nanotubes are 2 to 5 wt%. Claim 10 An anode assembly comprising an anode current collector and an anode coated on the anode current collector; wherein the anode comprises 70 to 95 wt% manganese dioxide; 2 to 20 wt% a conductive material containing carbon nanotubes; and 3 to 10 wt% a binder containing a cross-linked copolymer between polyacrylic acid and polyvinyl alcohol; and the loading amount of the anode is 10 mg / cm² 2 Aqueous zinc secondary battery characterized by the above. Claim 11 A water-based zinc secondary battery according to claim 10, characterized in that the copolymer is cross-linked with a composition ratio of 70 to 95 wt% polyacrylic acid and 5 to 30 wt% polyvinyl alcohol. Claim 12 A water-based zinc secondary battery according to claim 11, characterized in that the carbon nanotubes are 2 to 5 wt%.

Citation Information

Patent Citations

  • Binder for lithium ion secondary battery electrode, and its utilization

    JP2001076731A

  • Printed energy storage device

    US20180198136A1